Simulation of sonar reverberation signal considering the ocean multipath and Doppler effect - Zhang, Sen; Wu, Jian; Yin, Tianqi (Frontiers in Marine Science, 2023)
In order to achieve accurate modeling and simulation of sonar reverberation signals, four types of multi-path underwater reverberation models are established considering Doppler effect under the condition of separating the sound source and hydrophone. The simulation of underwater reverberation signals under static or uniform linear motion conditions is carried out for single point for the separating the sound source and hydrophone transceiver, as well as horizontal linear array. The non-stop-and-hop model of reverberation signals is presented. And the underwater reverberation signals in the array element domain and beam domain are obtained. From the simulation results of the improved model, it can be seen that the spatiotemporal two-dimensional characteristics and Doppler expansion are consistent with theoretical analysis. The frequency shift of the horizontal linear array reverberation signal is approximately sinusoidal with the directionality angle of the linear array. Comparing the simulation results of the improved model with traditional models, the improved model can more accurately simulate sonar reverberation signals.